Correlation of CD4+ count and viral load with urinary tract infection and antimicrobial resistance pattern of bacterial uropathogens among HIV patients in Wolaita Sodo, South Ethiopia - Hantalo, Admasu Haile; Shano, Abera Kumalo; Meja, Tekilu Israel (Frontiers in Microbiology, 2024)
Background: The permanence of HIV patients in healthcare provision center expose their weak immunity to different nosocomial microorganisms that migrate into and out of the hospital environment. The incidence of bacterial infections including urinary tract infection was inversely correlated with CD4+ T cells. Urinary tract infection (UTI) is one of the clinical problems among HIV patients. There was scarcity of published data on the relationship between viral load and CD4+ level and UTI. The aim of this study was to assess the relationship of viral load and CD4 with bacterial UTI among HIV patients Results: In this study, the overall prevalence of urinary tract infection (UTI) was 13.7%. E.coli, S.aureus, P.auroginosa, S.saprophyticus, P.mirabilis and K.pneumoniae were bacterial uropathogens detected in this study. E.coli (45.7%) was the predominant followed by S.aureus (14.3%). Positive correlation of CD4+ count and urinary tract infection was detected and found statistically significant (r=0.288 p>0.01) whereas the viral load and urinary tract infection negatively correlated and showed statistically significant association (p<0.01). Resistance rate of E.coli was 94%, 75% and 69% to ciprofloxacin, norfloxacin and cefepime, respectively. This study depicted 94% and 75% resistance of E.coli to amoxicillin-clavulanicand tetracyclin, respectivley. K.peuomoniae showed complete resistance (100%) to amoxicillin-clavulanic acid, tetracycline, and trimethoprim-sulfamethoxazole, where 100% susceptibility was detected to ciprofloxacin and nitrofurantoin. The magnitude of the multi-drug resistance (MDR) in the current study was 80%. CD4+ count, combination of ART drugs, and history of hospitalization were risk factors for urinary tract infection.In the current study, urinary tract infection was significant health concern among people living with HIV following their ART. The occurrence of urinary tract infection among HIV patients could be multifactorial factors that need further study. CD4+ count was positively correlated with the prevalence of UTI whereas viral load was negatively correlated. CD4+ count, combination of ART, and history of hospitalization were independent risk factors of UTI. MDR bacterial pathogens were seriously high and thus treatment of UTI HIV patients should be prescribed based on antibacterial susceptibility testing results.